James Joyce$1 (Bs Teaching Life and Methodss Language and Pedagogy in A Portrait of the Artist as a Young Man, Ulysses, and Finnegans Wake - Switaj, Elizabeth; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Before Joyce became a famous writer, he supported himself through his other language work: English-language teaching. The importance of James Joyce's teaching, however, has been underestimated until now. Closely reading Joyce's famed works, Switaj shows the influence of Joyce's brief career as an English teacher on the development of his canon.
Keywords: Science; Science; Science, general; Electronic books